Auditoría financiera a la cooperativa de transportes pesados “Trans Magdalena” de la ciudad de Latacunga, provincia de Cotopaxi, ubicada en la av. cinco de junio, en el periodo 01 de enero al 30 de junio del 2012 - Cevallos Méndez, Carmen de las Mercedes (2013)
The present research work had the general objective of developing a financial audit (COOPERATIVA DE TRASPORTES PESADOS “TRANS MAGDALENA”) FROM COTOPAXI, Latacunga City, to verify the reasonable less and confidential record of the accounting information the period 2012 providing a better supervision in the control and management of financial information. The methods and instruments for the analysis and collect information were the interview and survey which facilitated the evaluation of internal control in the company. It concluded the financial audit and it determined that the lack of information in a financial Administrative doesn`t have a good management also it doesn’t have a reliable internal control system. It proposes by the report of Financial Audit conclusions and recommendation will serve in order to improve the management of the company.